Characterization of Bottom Ash Waste Adsorbent from Palm Oil Plant Boiler Burning Process to Adsorb Carbon Dioxide in a Fixed Bed Column - Novi Sylvia; Fitriani Fitriani; Rozanna Dewi; Rizka Mulyawan; Abrar Muslim; Husni Husin; Yunardi Yunardi; Mutia Reza (Indonesian Journal of Chemistry, 2021)
Palm oil bottom ash utilization from mill boilers as CO2 adsorbent has been in use for few years. This study aims to examine adsorbent characteristics and capabilities of bottom ash produced from boiler combustion in palm oil industry for CO2 adsorption before and after utilization, such as compound functional group using the Fourier Transform Infra-Red (FT-IR) spectrophotometer, adsorbent morphology through Scanning Electron Microscopy (SEM), and compound amount using Energy Dispersive X-Ray Spectroscopy (EDX). The CO2 adsorption was carried out in fixed-bed column. Process variables consist of volumetric flow rate, contact time and bed height. Results showed that SiO2 compounds in the heterogeneous form with average particle size of 1073 nm, as supported by FT-IR spectrum finding indicating SiO2 signal at wavelength of 958–954 cm–1. Additionally, EDX analysis showed Silica and Oxygen content of 11.88% and 36.90%, resulting 70% CO2 adsorption capacity of 0.350 mg/g at discharge of 5 L/min, contact time of 40 min, and bed height of 12 cm. Langmuir isotherm model was obtained with R2 of 0.998, qm of 1.588, and kL of 0.144. Meanwhile, the kinetic model followed a simple first-order prototypical with R2 of 0.952, C02 of 0.260, and k1 of 0.006.